Ekspresi Inkulturasi Budaya NTT dalam Liturgi sebagai Perjumpaan Iman dan Budaya - Margareta Vera Lema; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article aims to understand how cultural expressions of East Nusa Tenggara (NTT) are inculturated in the liturgy of the Catholic Church as a manifestation of a dynamic encounter between Christian faith and local culture. The research method used is qualitative with a desk observation approach, which involves an in-depth study of Church documents, biblical texts, and practices of contextual liturgical analysis in various regions of NTT. The main results of the study indicate that the process of cultural inculturation in the liturgy in NTT not only enriches the forms of expression of the faith of the people, but also deepens the meaning and experience of the liturgy as a space for authentic theological dialogue between the Gospel message and local cultural heritage. Furthermore, this inculturation emphasizes the relevance of faith in the socio-cultural context, where local elements such as music, dance, clothing, and symbolism are brought to life to reveal the mystery of Christ more contextually. The theological and pastoral implications of these findings are that the Catholic Church in Indonesia, particularly in NTT, is a living, contextual, and relevant witness to the faith, demonstrating that the Gospel can be firmly embedded in the local land and culture, while strengthening the religious identity of the people amidst cultural plurality.